2012
DOI: 10.1186/1471-2458-12-632
|View full text |Cite
|
Sign up to set email alerts
|

The Cedar Project: high incidence of HCV infections in a longitudinal study of young Aboriginal people who use drugs in two Canadian cities

Abstract: BackgroundFactors associated with HCV incidence among young Aboriginal people in Canada are still not well understood. We sought to estimate time to HCV infection and the relative hazard of risk factors associated HCV infection among young Aboriginal people who use injection drugs in two Canadian cities.MethodsThe Cedar Project is a prospective cohort study involving young Aboriginal people in Vancouver and Prince George, British Columbia, who use illicit drugs. Participants’ venous blood samples were drawn an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 25 publications
3
55
0
2
Order By: Relevance
“…In total, we included 21 published studies 14,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] and seven unpublished studies [33][34][35][36][37]59,60 comprising 1827 HCV incident infections and 8789.7 person-years of follow-up. Overall HCV infection incidence ranged between 0.09 and 42 cases per 100 person-years across the studies.…”
Section: Study Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…In total, we included 21 published studies 14,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] and seven unpublished studies [33][34][35][36][37]59,60 comprising 1827 HCV incident infections and 8789.7 person-years of follow-up. Overall HCV infection incidence ranged between 0.09 and 42 cases per 100 person-years across the studies.…”
Section: Study Selectionmentioning
confidence: 99%
“…Twenty-one of the included studies reported the impact of OST, 14,20,39,40,[45][46][47]49,[51][52][53]55,57,58 including seven unpublished estimates. [33][34][35][36][37]59,60 Seventeen studies reported the impact of NSPs, 14,20,[41][42][43][44]47,48,50,54,56,58 including five unpublished sources, [33][34][35]59,60 and four reported combined measures of NSPs with OST, 14,33,44,47 including one unpublished data source.…”
Section: Type Of Interventionsmentioning
confidence: 99%
See 3 more Smart Citations